2004
DOI: 10.1111/j.1365-2125.2004.02111.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of APOMINE™: A meta‐analysis in cancer patients and healthy males

Abstract: Aims 1)To characterize the population pharmacokinetics of apomine in healthy males and in male and female patients with solid tumours and 2) to understand more fully the influence of induction and between-and within-subject variability on exposure to drug using Monte Carlo simulation. MethodsApomine was administered once-or twice-daily with or without food in single and multiple oral doses of 30-2100 mg to healthy males ( n = 19) and patients with solid tumours ( n = 19). The data were divided into model devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Other explanations are not immediately apparent. The plasma levels obtained were comparable to those found in other studies [9]. These may not, however, reflect intracellular concentrations of the drug and they may not have been sufficient to obtain the desired effect(s).…”
Section: Discussionsupporting
confidence: 87%
“…Other explanations are not immediately apparent. The plasma levels obtained were comparable to those found in other studies [9]. These may not, however, reflect intracellular concentrations of the drug and they may not have been sufficient to obtain the desired effect(s).…”
Section: Discussionsupporting
confidence: 87%
“…Since the number of estimated parameters in the final model was not high, the generated matrix of standardized parameters (fixed effects and variance components) did not allow principle component analysis (PCA) to be carried out on each component alone [19]. However, when PCA was performed on the full matrix of parameters, no influential individuals were identified, confirming the results obtained above.…”
Section: Resultssupporting
confidence: 66%
“…It was reported that the mean plasma AAG concentrations in breast, lung and ovary cancers were two‐fold higher than that in the healthy population . A lower clearance of drugs such as apomine and tipifarnib in oncology patients compared with HV was attributed to their lower free fraction, due to binding with high affinity for AAG .…”
Section: Discussionmentioning
confidence: 99%